2012
DOI: 10.1371/journal.pbio.1001300
|View full text |Cite
|
Sign up to set email alerts
|

Social Transfer of Pathogenic Fungus Promotes Active Immunisation in Ant Colonies

Abstract: Social contact with fungus-exposed ants leads to pathogen transfer to healthy nest-mates, causing low-level infections. These micro-infections promote pathogen-specific immune gene expression and protective immunization of nest-mates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
243
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 190 publications
(251 citation statements)
references
References 92 publications
2
243
3
3
Order By: Relevance
“…ants-as well as termites-rarely contract the disease and die after contact with Metarhizium-exposed nest-mates [21,32,39,40]. For L. neglectus, this fraction was as low as 2% (3/150 [32]) at the present pathogen dose, which is equivalent to a lethal dose of approximately 60% when applied to L. neglectus ants in the absence of social interactions (mortality isolated ants ).…”
Section: (B) Modelmentioning
confidence: 69%
See 3 more Smart Citations
“…ants-as well as termites-rarely contract the disease and die after contact with Metarhizium-exposed nest-mates [21,32,39,40]. For L. neglectus, this fraction was as low as 2% (3/150 [32]) at the present pathogen dose, which is equivalent to a lethal dose of approximately 60% when applied to L. neglectus ants in the absence of social interactions (mortality isolated ants ).…”
Section: (B) Modelmentioning
confidence: 69%
“…We use a basic model similar to Konrad et al [32], but here focus on the contraction of disease, i.e. neither addressing the effect of immunization (as in [32]) nor the effect of pathogen spread per se (as in [36]).…”
Section: (B) Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Even more, low-level infections may interfere with the predictions. Recently, it was shown that lowlevel infections with Metarhizium acquired by social contact in social insect colonies can lead to a protective immune stimulation Konrad et al (2012). This may well be true also for solitary individuals.…”
Section: Resultsmentioning
confidence: 98%